MEMBANGUN M-LEARNING DI PROGRAM STUDI TEKNIK INFORMATIKA UNIVERSITAS SAHID SURAKARTA - Faisah Yuniar; Sri Huning Anwariningsih; Astri Charolina (Universitas Sahid Surakarta, 2017)
The learning process in informatics department at Sahid University of Surakarta, the material of subject is distributed manually by copying file with the flash(disk) or use the book/ learning module teaching. Based on these problems, the writer build the mobile learning based on android as solution of these problem. The purpose of this study is build the mobile learning based on android to facilitate lecturers in presenting the materials to students using the smartphone so that will support the learning process in informatics department at Sahid University of Surakarta. The mobile learning application based on android is using object-oriented programming method, implemented by using java programing language, the application server is using databased based on web, and the system testing is using blackbox testing method. This mobile learning application had the features to facilitate students for downloading the required materials or facilitate student to looking for a materials that can be read anytime and anywhere. Otherwise it would be easier for the lecturers in the content of subject by uploading the files so that students can access the material via smartphone. Based on the results of testing mobile applications learning outcomes that have been tested 100% run functionally assessed by looking at the results of tests conducted of three university students by using an Android device with 3 different smarthpone OS, it can be concluded that the speed of opening the main menu can be known that average of loading time (±0, 59s), speed of access (±6, 32s), and download speeds (±9s).